Erupting complex odontoma: Report of a rare case - Pinakapani Ramakrishna; Nallan CSK Chaitanya; Pavan Kumar Yellarthi; Nisheeth Saawarn (Wolters Kluwer Medknow Publications, 2014)
Odontomas are the most frequent hamartomatous lesions involving the oral cavity. The complex variant is an agglomerate of all dental tissues characterized by abnormal morphodifferentiation despite normal histodifferentiation. These are usually asymptomatic and are frequently associated with eruption disturbances. We report an unusual case of erupting complex odontoma associated with an impacted maxillary second molar.